Investigating the differential effectiveness of a teacher professional development programme for rural and urban classrooms in Indonesia. Issue 5 (19th October 2016) - Soebari, Titien; Aldridge, Jill M.
Abstract : This article reports on the differential effectiveness of a teacher professional development programme for teachers in urban and rural schools in Indonesia. The study employed an embedded mixed methods design that involved the concurrent collection of both quantitative and qualitative data. The quantitative component involved a pre–post design in which two surveys were administered to a sample of 2417 students drawn from 66 classes in 32 lower secondary schools (960 from urban schools and 1457 from rural schools). The qualitative component involved six case study teachers and two students from each of their classes. Qualitative information was gathered using teacher and student interviews, classroom observations and teacher reflective journals. The quantitative results suggested that there were disparities between the usefulness of the knowledge and skills imparted during the programme for teachers in urban and rural schools. The themes that emerged from the data gathered using qualitative methods helped to make sense of the differences in student scores in urban and rural schools before and after the teacher professional development programme.